Homologação de sistemas fotovoltaicos com potência superior a 10 kW: procedimentos, projetos e instalação - QUEIROZ, Maria Alinne Sousa (2024)
The growing use of photovoltaic systems in Brazil, especially those with a power output of more than 10 kW, classified as distributed microgeneration, has required increasingly detailed regulations to ensure their safe and efficient integration into the electricity grid. This work is based on the Internship Report carried out at the company SOL & CIA - Solar Energy and regulations in force for approving a photovoltaic system of more than 10 kW in the city of Tucuruí-PA. To this end, the technical requirements established by the National Electric Energy Agency (ANEEL) and Equatorial Energia - Pará were studied, as well as the guidelines of the applicable technical standards. Among the challenges identified are bureaucratic procedures, the standardization of processes between distributors and the monitoring of technological and regulatory updates. Finally, this study proposes a step-by-step approach to optimize the approval process.